KELELAHAN DAN TEGANGAN YANG DIIZINKAN PADA SAMBUNGAN LAS - Kemas Rifan (Mesin, 1997)
Welded joints loaded cyclically are prone to fatigue because they provide srress concentrations due to geometry changes, weld proï¬le shapes and microscopic defects in the welds